Barriers to venipuncture-induced pain prevention in cancer patients: a qualitative study. Issue 1 (December 2017) - Filbet, Marilène; Larkin, Philip; Chabloz, Claire; Chirac, Anne; Monsarrat, Léa; Ruer, Murielle; Rhondali, Wadih; Collin, Cyrille
Abstract Background Procedural pain reduces the quality of life of cancer patients. Although there are recommendations for its prevention, there are some obstacles for its management. The purpose of this study was to analyze the barriers to procedural pain prophylaxis in cancer patients reflecting the views of the nurses. Methods We used qualitative methodology based on semi-structured interviews conducted with nurses, focusing on practices of venipuncture-induced and needle change for implantable central venous access port (ICVAP) pain management in cancer patients. A thematic analysis approach informed the data analysis. Results Interviews were conducted with 17 nurses. The study highlighted 4 main themes; technical and relational obstacles, nurses' professional recognition, the role of the team, and organizational issues. Participants understood the painful nature of venipuncture. Despite being aware of the benefits of the anesthetic patch, they did not utilize it in a systematic way. We identified several barriers at different levels: technical, relational and previous experience of incident pain. Several organizational issues were also highlighted (e.g. lack of protocol, lack of time). Conclusions The prevention of venipuncture-induced cancer pain requires a structured training program, which should reflect the views of nurses in clinical practice.